Statistical study of the void structure of Bi2212 multifilamentary superconducting wires and its effect on the critical current density. Issue 8 (20th September 2019) - Zhou, Xin-Xin; Xue, Feng; Gou, Xiaofan; Shen, Teng-Ming
Abstract : Purpose: Multifilamentary Bi2 Sr2 CaCu2 Ox (Bi2212) superconductor composite wires are the only high-temperature superconducting round wires (RW) with sufficient critical current density ( Jc ) for superconducting magnets generating magnetic fields greater than 25 Tesla. Very complex microstructures of Bi2212 RWs including the voids or gas bubbles, filament to filament bridges and wire architecture strongly influence their electrical behavior. Especially, a large number of voids in Bi2212 superconducting filaments is believed to be the major current-limiting mechanism. However, the effect of the void structure on the Jc is not well understood yet. Design/methodology/approach: In this paper, the authors first statistically analyzed the size and distribution of voids in filaments using the reported microscopic data, obtaining the essential statistical regularities. An electrical model was further developed to predict the Jc of multifilamentary wires while taking into account of the current limiting mechanisms of the void structure in filaments, and the current sharing roles of filament to filament bridges. Findings: The model predicts the quantitative dependence of Jc on the number of Bi2212 filaments in each bundle of a double-restack wire and porosity. The results are useful optimizing design and fabrication of Bi2212 multifilamentary wires. Originality/value: For the complex structure of voids and interfilamentary bridges inside Bi2212 multifilamentary superconducting wires, the authors took a statistical characterization and studied its effect on the critical current density Jc (the key index of evaluating the current carrying capacity).